Comparative histochemical study of the kidney of six mammalian species - Oghoverere, Abiokuta Blessing; Igho, Odokuma Emmanuel (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Comparative anatomy describes the similarities and differences in the anatomy of different species. Comparative anatomical studies do not only provide evidence for evolution but also indicate that various organisms originate from a common ancestor. They assist scientists in classifying these organisms based on similar characteristics of their anatomical structure. The aim of this study was to compare histochemical of the kidney of six mammalian species. The animals were grouped into three based on their dietary patterns i.e herbivores (Capra aegagrus and Bos taurus), carnivores (Canis lupus and Felis catus) and omnivores (Rattus norvegicus and Sus scrofa). Tissues were obtained from each of the studied species and preserved in 10% formal saline for one week until analysis. The tissues were then subsequently processed and stained using general and specific histochemical techniques. It was observed from this study all the mammalian kidneys consisted of similar histological features which explained that these studied mammals undergo the same evolutionary trend, adaptational changes and phylogenic relationship that exist between the kidneys of the studied species. Despite their differences in dietary patterns, the studied species have similar histological features with little observed variation. However, they have little differences in histochemical staining pattern for glycogen and glycoprotein but in reticulin they all stain intensely. This study has established a strong relationship in the histology of the kidney in six mammalian species.